Thermal shock resistant fireproof material and preparation method and application thereof

By combining methylphenyl vinyl silicone oil/silicon resin into the impact resistance layer and combining it with the fire-resistant ceramic layer and the glass fiber layer, the problem of existing fire-resistant materials being easily damaged under high temperature thermal shock is solved, and the dual effects of thermal shock and fire-proof and heat insulation are achieved.

CN119734494AActive Publication Date: 2025-04-01CYBRID TECHNOLOGIES INC

Patent Information

Application Number
CN202411844630.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-01
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Existing fire-proof materials are easily destroyed under high temperature and thermal shock, resulting in fire or explosion accidents, and the process is complex and costly.

Method used

By combining methylphenyl vinyl silicone oil/silicon resin into the impact layer, the temperature resistance of the impact layer is improved, and working together with the fire-resistant ceramic layer and the glass fiber layer, the dual effects of thermal shock resistance and fire-proof and heat insulation are formed.

Benefits of technology

At short-term high temperatures above 350°C, the impact resistance layer remains intact, gaining time for the fire-proof ceramic layer, enhancing the compactness of the impact resistance layer after high temperatures, reducing the ablation rate, and achieving effective fire-blocking and fire-proof performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a thermal shock resistant fireproof material and a preparation method and application thereof, and belongs to the technical field of fireproof materials. The thermal shock resistant fireproof material comprises an impact resistant layer, a fireproof ceramic layer arranged on the impact resistant layer and a glass fiber layer arranged between the impact resistant layer and the fireproof ceramic layer, the anti-impact layer is prepared from the following raw material components in parts by mass: 40 to 50 parts of first silicon rubber, 0.2 to 1.0 part of first curing agent, 0.3 to 0.5 part of first reaction aid and 45 to 60 parts of filler; the fireproof ceramic layer comprises the following raw material components in parts by mass: 30-40 parts of second silicone rubber, 0.5-2 parts of a second curing agent, 0-0.5 part of a second reaction aid, 0.3-1.5 parts of a coupling agent, 20-30 parts of an inorganic flame-retardant filler and 35-45 parts of an inorganic ceramic filler, so that the thermal-shock-resistant fireproof material has excellent thermal shock resistance and fireproof and heat-insulating properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fireproof materials, and in particular relates to a heat shock resistant fireproof material and a preparation method and application thereof. Background Art

[0002] In recent years, with the vigorous development of the new energy vehicle industry, the market has greatly increased the endurance and charging efficiency of power batteries, so high rate, high capacity and good cycle performance are the main development trends of lithium batteries. As the energy density of lithium-ion power batteries has been increasing, the battery life has been extended, and there have been more and more incidents of spontaneous combustion and explosion of lithium-ion batteries; thermal runaway may occur under conditions of overcharging, short circuit, high temperature, impact, etc., and a large amount of high-temperature impact force may be released instantly. The local temperature may even reach thousands of degrees Celsius, melting the metal shell, causing a chain reaction leading to fire or even explosion accidents, causing huge losses to related companies and users.

[0003] Chinese invention patent CN 112928362A discloses a multi-layer fireproof material for batteries and its manufacturing method, including a fireproof material substrate and a protective layer coated on the outer surface of the fireproof material substrate; the fireproof material substrate includes a first glass fiber cloth layer, a ceramic silicone rubber layer, and a second glass fiber cloth layer from top to bottom; the multi-layer fireproof material disclosed in the invention has significant flame retardant and fireproof effects, good weather resistance and environmental protection performance, sufficient resistance to high temperature flame impact, and good mechanical properties. However, the fireproof material of this invention has a five-layer structure, poor flexibility, and is difficult to adapt to the requirements of different working conditions; and the process is complicated, the processing is difficult, and the cost is high.

[0004] Chinese invention patent CN 118271850A discloses a flame retardant and fire resistant silicone rubber material and its preparation method. The flame retardant and fire resistant silicone rubber material is prepared from the following raw materials in mass percentage: 1%-5% hydrogenated silicone oil, 4%-6% vinyl silicone oil, 2%-4% hydroxy silicone oil, 18%-22% compounded flame retardant filler, 8%-12% carbon black, 0.5%-1.0% silane coupling agent, 0.1%-0.2% release agent, 0.1%-0.3% platinum catalyst, 0.1%-0.2% inhibitor, and the balance is raw rubber. The silicone rubber material has good flame retardant and fire resistant properties at a relatively low flame retardant filler addition amount, while reducing the overall production cost. However, although this method improves flame retardant properties and flexibility, it is not resistant to high temperature thermal shock, is not heat-insulated, requires various pretreatments during the preparation process, and has a high manufacturing cost.

[0005] Therefore, there is an urgent need for a fireproof material that can resist thermal shock to provide fireproof coating for the battery. Even in the face of extreme thermal runaway, the high temperature shock will not completely destroy the structure and cause more losses. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a heat shock resistant fireproof material and a preparation method and application thereof. The temperature resistance of the impact resistant layer is improved by compounding methylphenyl vinyl silicone oil / silicone resin in the impact resistant layer, so that the use temperature range of the heat shock resistant fireproof material is better, and the maximum short-term high temperature resistance can reach above 350°C, which is beneficial to the formation of the impact resistant layer, while reducing the ablation rate and enhancing the density of the impact resistant layer after high temperature; together with the composite filler, it is quickly melted and sintered at a relatively low temperature to form a solid impact resistant layer; when facing high-temperature thermal shock, it can block the flame for the glass fiber layer while buying time for sufficient ceramicization of the fireproof ceramic layer, thereby playing a dual role of heat shock resistance and fireproofing and heat insulation.

[0007] The first object of the present invention is to provide a heat shock resistant fireproof material, comprising an impact resistant layer, a fireproof ceramic layer disposed on the impact resistant layer, and a glass fiber layer disposed between the impact resistant layer and the fireproof ceramic layer;

[0008] The raw material components and their weight parts of the impact-resistant layer are: 40-50 parts of the first silicone rubber, 0.2-1.0 parts of the first curing agent, 0.3-0.5 parts of the first reaction aid and 45-60 parts of the filler; the first silicone rubber includes the first methyl vinyl silicone oil, methyl phenyl vinyl silicone oil and methyl phenyl vinyl silicone resin; the first curing agent includes the first hydrogen-containing silicone oil and methyl phenyl hydrogen-containing silicone resin; the filler includes the first silazane-treated fumed silica, silicon powder, lithium carbonate, sodium carbonate and wollastonite;

[0009] The raw material components of the fireproof ceramic layer and their mass parts are: 30-40 parts of second silicone rubber, 0.5-2 parts of second curing agent, 0-0.5 parts of second reaction aid, 0.3-1.5 parts of coupling agent, 20-30 parts of inorganic flame retardant filler, and 35-45 parts of inorganic ceramic filler.

[0010] In one embodiment of the present invention, the silicone rubber includes the first methyl vinyl silicone oil, methyl phenyl vinyl silicone oil and methyl phenyl vinyl silicone resin in a mass ratio of (30-45):(1-5):(2-6).

[0011] Further, the viscosity of the first methyl vinyl silicone oil is 1000mPas-5000mPas, and the vinyl content is 0.2%-1.0%;

[0012] The methylphenyl vinyl silicone oil has a phenyl mole fraction of 5%-15%, a viscosity of 1000mPas-6000mPas, and a vinyl content of 0.1%-0.5%;

[0013] The methylphenyl vinyl silicone resin has a phenyl mole fraction of 20%-40%, a viscosity of 1000mPas-10000mPas, and a vinyl content of 0.5%-1.5%.

[0014] In one embodiment of the present invention, the mass ratio of the first hydrogen-containing silicone oil to the methylphenyl hydrogen-containing silicone resin is (0.7-0.9):(0.1-0.3). By compounding the hydrogen-containing silicone oil and the methylphenyl hydrogen-containing silicone resin, the material can have high temperature resistance and sufficient flexibility.

[0015] Further, the hydrogen content of the first hydrogen-containing silicone oil is 0.18-1.5%;

[0016] The hydrogen content of the methylphenyl hydrogenated silicone resin is 0.2-0.5%.

[0017] In one embodiment of the present invention, the mass ratio of the first silazane-treated fumed silica, silicon powder, lithium carbonate, sodium carbonate and wollastonite is (20-27):(5-10):(14-20):(2-5):(4-6).

[0018] Furthermore, the specific surface area of ​​the first silazane-treated fumed silica is 100 m 2 / g-250m 2 / g;

[0019] The particle sizes of the silicon micropowder and wollastonite are D50≤10μm and D90≤50μm. By compounding different fillers and limiting the particle sizes, the impact-resistant layer can be made thin enough and achieve the effect of thermal shock resistance.

[0020] In one embodiment of the present invention, the first reaction aid is selected from a first alkynol inhibitor and / or a first platinum catalyst.

[0021] Furthermore, the platinum content of the first platinum catalyst is 1000ppm-3000ppm.

[0022] In one embodiment of the present invention, the second silicone rubber is selected from one or more of a second methyl vinyl silicone oil, a methyl vinyl silicone resin and a methyl vinyl silicone rubber raw rubber; further, the molecular weight of the methyl vinyl silicone rubber raw rubber is 400,000-650,000, and the vinyl content is 0.05%-3.5%;

[0023] The second curing agent is selected from one or more of a second hydrogen-containing silicone oil, bis(2,4-dichlorobenzoyl) peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;

[0024] The second reaction aid is selected from one or more of a release agent, a second acetylene alcohol inhibitor and a second platinum catalyst; further, the release agent is zinc stearate; the platinum content of the second platinum catalyst is 1000ppm-3000ppm;

[0025] The coupling agent is selected from one or more of γ-methacryloxypropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, dodecyltrimethoxysilane and vinyltrimethoxysilane;

[0026] The inorganic flame retardant filler is selected from one or more of aluminum hydroxide, magnesium hydroxide, benzotriazole and carbon black; preferably, the inorganic flame retardant filler includes aluminum hydroxide and carbon black; the mass ratio of aluminum hydroxide to carbon black is (18-25):(1-3); the particle size of the aluminum hydroxide is D50≤10μm, D90≤50μm; by compounding different inorganic flame retardant fillers and limiting the particle size, the fireproof ceramic layer can be made into a sufficiently thin thickness while having sufficient flame retardant properties.

[0027] The inorganic ceramic filler is selected from one or more of mica powder, clay, glass powder, zinc borate, diatomaceous earth, zinc oxide, fumed silica treated with a second silazane, aluminum oxide, and magnesium oxide; preferably, the inorganic ceramic filler comprises mica powder, glass powder, zinc borate, diatomaceous earth, and fumed silica treated with a second silazane, and the mass ratio of the mica powder, glass powder, zinc borate, diatomaceous earth, and fumed silica treated with a second silazane is (20-25):(2-5):(4-10):(3-6):(1-3); the particle sizes of the mica powder, glass powder, zinc borate, and diatomaceous earth are D50≤10μm, and D90≤50μm; the specific surface area of ​​the fumed silica treated with the second silazane is 100m 2 / g-250m 2 / g.

[0028] In one embodiment of the present invention, the thickness of the impact-resistant layer is 0.2 mm-0.5 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, etc.;

[0029] The thickness of the glass fiber layer is 0.2 mm-0.8 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, etc.;

[0030] The thickness of the fireproof ceramic layer is 0.4 mm-2.0 mm, for example, it can be 0.4 mm, 0.6 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, etc.

[0031] The second object of the present invention is to provide a method for preparing the thermal shock resistant fireproof material, comprising the following steps:

[0032] S1, adding filler, first curing agent and first reaction aid to the first silicone rubber in sequence and stirring evenly to obtain impact-resistant layer glue;

[0033] S2, adding an inorganic ceramic filler, a coupling agent, an inorganic flame retardant filler, a second reaction aid and a second curing agent to the second silicone rubber in sequence and stirring evenly to obtain a fireproof ceramic layer glue;

[0034] S3, rolling the fireproof ceramic layer adhesive described in S2 on one side of the glass fiber layer, and coating the impact-resistant layer adhesive described in S1 on the other side to obtain the heat-shock-resistant fireproof material.

[0035] In one embodiment of the present invention, in S2, when the inorganic ceramic filler, coupling agent, and inorganic flame retardant filler are added, the temperature of the rubber material is 80°C-100°C;

[0036] When the second reaction aid and the second curing agent are added, the temperature of the rubber compound is 15°C-40°C.

[0037] The third object of the present invention is to provide an application of the thermal shock resistant fireproof material in new energy power batteries.

[0038] The technical solution of the present invention has the following advantages over the prior art:

[0039] The heat shock resistant fireproof material of the present invention defends against the high-temperature thermal shock force when the battery is out of control through the shock resistant layer. Methylphenyl vinyl silicone oil / silicone resin is compounded in the shock resistant layer to improve the temperature resistance of the shock resistant layer, so that it can remain intact at a short high temperature of 350°C, buying time for the ceramicization of the fireproof ceramic layer later. At the same time, the methylphenyl vinyl silicone oil / silicone resin has a lower ablation rate, and more silicon dioxide and gas-phase silicon dioxide can remain after ablation to combine and fill each other, which can make the shell more solid after ablation; at the same time, the fillers lithium carbonate and sodium carbonate compounded in the shock resistant layer can reduce the sintering temperature of silicon micropowder, wollastonite and silazane-treated gas-phase silicon dioxide, so that it can be quickly sintered into a solid shell at a lower temperature to offset part of the thermal shock force; in this way, when facing high-temperature thermal shock, the overall material can exert perfect barrier fireproof performance. In addition, the subsequent fireproof ceramic layer has enough time to ceramicize at high temperature, forming a fireproof ceramic layer with a hard shell and porous structure. While further blocking the flame, the porous structure and the sealed structure can isolate the temperature and voltage current, achieving the effect of heat insulation and electrical insulation. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.

[0041] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.

[0042] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.

[0043] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.

[0044] In the present invention, unless otherwise specified, the methyl vinyl silicone oil used in the examples of the present invention has a viscosity of 1000 mPas and a vinyl content of 0.28%.

[0045] In the present invention, unless otherwise specified, the methylphenyl vinyl silicone oil used in the embodiments of the present invention has a phenyl molar fraction of 10%, a viscosity of 2500 mPas, and a vinyl content of 0.19%.

[0046] In the present invention, unless otherwise specified, the methylphenylvinyl silicone resin used in the embodiments of the present invention has a phenyl molar fraction of 37%, a viscosity of 6000 mPas, and a vinyl content of 0.85%.

[0047] In the present invention, unless otherwise specified, the specific surface area of ​​the fumed silica treated with silazane used in the examples of the present invention is 150 m 2 / g.

[0048] In the present invention, unless otherwise specified, the particle size D50 of the silicon micropowder used in the embodiments of the present invention is 1.5 μm, and D90 is 50 μm.

[0049] In the present invention, unless otherwise specified, the particle size D50 of the wollastonite used in the examples of the present invention is 5 μm, and the particle size D90 is 50 μm.

[0050] In the present invention, unless otherwise specified, the hydrogen content of the hydrogen-containing silicone oil used in the examples of the present invention is 0.75%.

[0051] In the present invention, unless otherwise specified, the hydrogen content of the methylphenyl hydrogenated silicone resin used in the examples of the present invention is 0.3%.

[0052] In the present invention, unless otherwise specified, the platinum content of the first platinum catalyst used in the examples of the present invention is 2000 ppm; the platinum content of the second platinum catalyst is 3000 ppm.

[0053] In the present invention, unless otherwise specified, the molecular weight of the first methyl vinyl silicone rubber used in the embodiments of the present invention is 620,000 and the vinyl content is 0.05%; the molecular weight of the second methyl vinyl silicone rubber is 620,000 and the vinyl content is 3.0%.

[0054] In the present invention, unless otherwise specified, the particle size D50 of the mica powder used in the embodiments of the present invention is 5 μm, and D90 is 45 μm.

[0055] In the present invention, unless otherwise specified, the particle size D50 of the glass powder used in the embodiments of the present invention is 3 μm, and D90 is 40 μm.

[0056] In the present invention, unless otherwise specified, the particle size D50 of the zinc borate used in the examples of the present invention is 2 μm, and the particle size D90 is 40 μm.

[0057] In the present invention, unless otherwise specified, the particle size D50 of the diatomaceous earth used in the examples of the present invention is 5 μm, and D90 is 40 μm.

[0058] In the present invention, unless otherwise specified, the particle size D50 of the aluminum hydroxide used in the examples of the present invention is 1.5 μm, and D90 is 40 μm.

[0059] Example 1

[0060] The thermal shock resistant fireproof material and preparation method thereof of this embodiment specifically include the following steps:

[0061] S1, add 32.5 parts of methyl vinyl silicone oil, 3.5 parts of methyl phenyl vinyl silicone oil and 4 parts of methyl phenyl vinyl silicone resin into a kneader and stir for 10 minutes; then add 25.7 parts of silazane-treated fumed silica, 9 parts of silicon powder, 16 parts of lithium carbonate, 3 parts of sodium carbonate, and 5 parts of wollastonite and continue stirring for 20 minutes; continue to add 0.7 parts of hydrogen-containing silicone oil, 0.3 parts of methyl phenyl hydrogen-containing silicone resin, and 0.03 parts of acetylene alcohol inhibitor and stir for 20 minutes; finally, add 0.27 parts of the first platinum catalyst and stir for 30 minutes to obtain an impact-resistant layer adhesive;

[0062] S2, add 32 parts of the first methyl vinyl silicone rubber raw rubber and 0.7 parts of the second methyl vinyl silicone rubber raw rubber into a kneader, heat to 80°C and stir for 10 minutes; keep the temperature at 80°C, add 24 parts of mica powder, 4 parts of glass powder, 8 parts of zinc borate, 5.5 parts of diatomaceous earth, 2 parts of silazane-treated fumed silica and 0.3 parts of γ-methacryloxypropyltrimethoxysilane and continue to stir for 20 minutes; continue to add 20 parts of aluminum hydroxide and 2 parts of carbon black and stir for 20 minutes; cool to room temperature, add 0.25 parts of zinc stearate and 0.25 parts of the second platinum catalyst and stir for 20 minutes; continue to add 1 part of bis(2,4-dichlorobenzoyl) peroxide and stir for 30 minutes to obtain a fireproof ceramic layer glue;

[0063] S3. Using glass fiber with a thickness of 0.2 mm as the support membrane, the fire-proof ceramic layer glue is calendered on the glass fiber through a calender to form a fire-proof ceramic layer with a thickness of 0.6 mm, and then rolled up; using the obtained roll as the base membrane, the impact-resistant layer glue is coated on the other side of the glass fiber through a coater to form an impact-resistant layer with a thickness of 0.2 mm, thereby obtaining a heat-shock-resistant fireproof material.

[0064] Example 2

[0065] The thermal shock resistant fireproof material and preparation method thereof of this embodiment specifically include the following steps:

[0066] S1, add 35.5 parts of methyl vinyl silicone oil, 3.5 parts of methyl phenyl vinyl silicone oil and 4 parts of methyl phenyl vinyl silicone resin into a kneader and stir for 10 minutes; then add 24.7 parts of silazane-treated fumed silica, 8 parts of silicon powder, 15 parts of lithium carbonate, 3 parts of sodium carbonate, and 5 parts of wollastonite and continue stirring for 20 minutes; continue to add 0.7 parts of hydrogen-containing silicone oil, 0.3 parts of methyl phenyl hydrogen-containing silicone resin, and 0.03 parts of acetylene alcohol inhibitor and stir for 20 minutes; finally, add 0.27 parts of the first platinum catalyst and stir for 30 minutes to obtain an impact-resistant layer adhesive;

[0067] S2, add 35 parts of the first methyl vinyl silicone rubber raw rubber and 0.7 parts of the second methyl vinyl silicone rubber raw rubber into a kneader, heat to 80°C and stir for 10 minutes; keep the temperature at 80°C, add 23 parts of mica powder, 3 parts of glass powder, 7 parts of zinc borate, 5.5 parts of diatomaceous earth, 2 parts of silazane-treated fumed silica and 0.3 parts of γ-methacryloxypropyltrimethoxysilane and continue to stir for 20 minutes; continue to add 20 parts of aluminum hydroxide and 2 parts of carbon black and stir for 20 minutes; cool to room temperature, add 0.25 parts of zinc stearate and 0.25 parts of the second platinum catalyst and stir for 20 minutes; continue to add 1 part of bis(2,4-dichlorobenzoyl) peroxide and stir for 30 minutes to obtain a fireproof ceramic layer glue;

[0068] S3. Using glass fiber with a thickness of 0.5 mm as the supporting film, the fire-proof ceramic layer glue is calendered on the glass fiber through a calender to form a fire-proof ceramic layer with a thickness of 1.2 mm, and then rolled up; using the obtained roll as the base film, the impact-resistant layer glue is coated on the other side of the glass fiber through a coater to form an impact-resistant layer with a thickness of 0.3 mm, thereby obtaining a heat-shock-resistant fireproof material.

[0069] Example 3

[0070] The thermal shock resistant fireproof material and preparation method thereof of this embodiment specifically include the following steps:

[0071] S1, add 42.5 parts of methyl vinyl silicone oil, 3.5 parts of methyl phenyl vinyl silicone oil and 4 parts of methyl phenyl vinyl silicone resin into a kneader and stir for 10 minutes; then add 20.7 parts of silazane-treated fumed silica, 5 parts of silicon powder, 15 parts of lithium carbonate, 3 parts of sodium carbonate, and 5 parts of wollastonite and continue stirring for 20 minutes; continue to add 0.8 parts of hydrogen-containing silicone oil, 0.2 parts of methyl phenyl hydrogen-containing silicone resin, and 0.03 parts of acetylene alcohol inhibitor and stir for 20 minutes; finally, add 0.27 parts of the first platinum catalyst and stir for 30 minutes to obtain an impact-resistant layer adhesive;

[0072] S2, add 38 parts of the first methyl vinyl silicone rubber raw rubber and 0.7 parts of the second methyl vinyl silicone rubber raw rubber into a kneader, heat to 80°C and stir for 10 minutes; keep the temperature at 80°C, add 20 parts of mica powder, 4 parts of glass powder, 6 parts of zinc borate, 3.5 parts of diatomaceous earth, 2 parts of silazane-treated fumed silica and 0.3 parts of γ-methacryloxypropyltrimethoxysilane and continue to stir for 20 minutes; continue to add 22 parts of aluminum hydroxide and 2 parts of carbon black and stir for 20 minutes; cool to room temperature, add 0.25 parts of zinc stearate and 0.25 parts of the second platinum catalyst and stir for 20 minutes; continue to add 1 part of bis(2,4-dichlorobenzoyl) peroxide and stir for 30 minutes to obtain a fireproof ceramic layer glue;

[0073] S3. Using glass fiber with a thickness of 0.8 mm as the supporting film, the fire-proof ceramic layer glue is calendered on the glass fiber through a calender to form a fire-proof ceramic layer with a thickness of 1.7 mm, and then rolled up; using the obtained roll material as the base film, the impact-resistant layer glue is coated on the other side of the glass fiber through a coater to form an impact-resistant layer with a thickness of 0.5 mm, thereby obtaining a heat-shock-resistant fireproof material.

[0074] Comparative Example 1

[0075] The method is basically the same as Example 1, except that the methylphenylvinyl silicone oil and methylphenylvinyl silicone resin are replaced by the first methylvinyl silicone rubber raw rubber.

[0076] Comparative Example 2

[0077] Basically the same as Example 1, except that no lithium carbonate is added.

[0078] Comparative Example 3

[0079] Basically the same as Example 1, except that no sodium carbonate is added.

[0080] Comparative Example 4

[0081] The method is basically the same as Example 1, except that the amount of silazane-treated fumed silica in the impact-resistant layer adhesive is adjusted from 25.7 parts to 5.7 parts.

[0082] Test Case

[0083] The thermal insulation properties and the like of the thermal shock resistant fireproof materials of Examples 1-3 and Comparative Examples 1-4 were tested;

[0084] Thermal insulation performance: burn at 1300±100℃ for 30min, test back temperature;

[0085] Thermal shock resistance: after 5 minutes of 1300±100℃ temperature and 1MPa gas shock, observe whether it is penetrated;

[0086] Fire resistance: Burn at 1300±100℃ for 30min, and observe whether it burns through;

[0087] Table 1 shows the final measured performance:

[0088] Table 1

[0089] Sample Thermal insulation performance Thermal shock resistance Fire performance Example 1 <500℃ No penetration No burn-through Example 2 <400℃ No penetration No burn-through Example 3 <400℃ No penetration No burn-through Comparative Example 1 >500℃ Punch through Burn through Comparative Example 2 >500℃ Punch through Burn through Comparative Example 3 >500℃ Punch through Burn through Comparative Example 4 >500℃ Punch through Burn through

[0090] It can be seen from Table 1 that the material of the embodiment is not easily punched through, has good impact resistance and good heat insulation.

[0091] By comparing Example 1 and Comparative Example 1, it can be seen that when phenyl silicone rubber is not introduced, the methyl vinyl silicone rubber in the material is rapidly ablated in large quantities when facing high-temperature thermal shock, forming a large number of densely packed holes inside the material, and the material loses its firmness and is easily penetrated.

[0092] By comparing Example 1 and Comparative Examples 2-3, it can be seen that when lithium carbonate or sodium carbonate is not introduced, the sintering temperature of silicon micropowder, wollastonite and silazane-treated fumed silica is very high. When subjected to thermal shock, it cannot be completely sintered into a solid shell, has very low strength, cannot offset the thermal shock force, and is easily penetrated.

[0093] Comparison of Example 1 and Comparative Example 4 shows that when the amount of silazane-treated fumed silica is insufficient, although it can be sintered into a dense shell, the strength of the constructed green body skeleton is not high. When subjected to thermal shock, it cannot offset the thermal shock force and is easily penetrated.

[0094] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A thermal shock resistant fireproof material, characterized in that: It comprises an impact-resistant layer, a fire-resistant ceramic layer arranged on the impact-resistant layer, and a glass fiber layer arranged between the impact-resistant layer and the fire-resistant ceramic layer; The raw material components and their weight parts of the impact-resistant layer are: 40-50 parts of the first silicone rubber, 0.2-1.0 parts of the first curing agent, 0.3-0.5 parts of the first reaction aid and 45-60 parts of the filler; the first silicone rubber includes the first methyl vinyl silicone oil, methyl phenyl vinyl silicone oil and methyl phenyl vinyl silicone resin; the first curing agent includes the first hydrogen-containing silicone oil and methyl phenyl hydrogen-containing silicone resin; the filler includes the first silazane-treated fumed silica, silicon powder, lithium carbonate, sodium carbonate and wollastonite; The raw material components of the fireproof ceramic layer and their mass parts are: 30-40 parts of second silicone rubber, 0.5-2 parts of second curing agent, 0-0.5 parts of second reaction aid, 0.3-1.5 parts of coupling agent, 20-30 parts of inorganic flame retardant filler, and 35-45 parts of inorganic ceramic filler.

2. The heat shock resistant fireproof material according to claim 1, characterized in that: The silicone rubber comprises a first methyl vinyl silicone oil, a methyl phenyl vinyl silicone oil and a methyl phenyl vinyl silicone resin in a mass ratio of (30-45):(1-5):(2-6).

3. The heat shock resistant fireproof material according to claim 1, characterized in that: The mass ratio of the first hydrogen-containing silicone oil to the methylphenyl hydrogen-containing silicone resin is (0.7-0.9):(0.1-0.3).

4. The heat shock resistant fireproof material according to claim 1, characterized in that: The mass ratio of the first silazane-treated fumed silica, silicon powder, lithium carbonate, sodium carbonate and wollastonite is (20-27):(5-10):(14-20):(2-5):(4-6).

5. The heat shock resistant fireproof material according to claim 1, characterized in that: The first reaction aid is selected from a first alkynol inhibitor and / or a first platinum catalyst.

6. The heat shock resistant fireproof material according to claim 1, characterized in that: The second silicone rubber is selected from one or more of a second methyl vinyl silicone oil, a methyl vinyl silicone resin and a methyl vinyl silicone rubber raw rubber; The second curing agent is selected from one or more of a second hydrogen-containing silicone oil, bis(2,4-dichlorobenzoyl) peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; The second reaction aid is selected from one or more of a release agent, a second acetylenic alcohol inhibitor, and a second platinum catalyst; The coupling agent is selected from one or more of γ-methacryloxypropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-aminopropyltrimethoxysilane, dodecyltrimethoxysilane and vinyltrimethoxysilane; The inorganic flame retardant filler is selected from one or more of aluminum hydroxide, magnesium hydroxide, benzotriazole and carbon black; The inorganic ceramic filler is selected from one or more of mica powder, clay, glass powder, zinc borate, diatomaceous earth, zinc oxide, fumed silica treated with a second silazane, aluminum oxide, and magnesium oxide.

7. The heat shock resistant fireproof material according to claim 1, characterized in that: The thickness of the impact-resistant layer is 0.2 mm to 0.5 mm; The thickness of the glass fiber layer is 0.2mm-0.8mm; The thickness of the fireproof ceramic layer is 0.4 mm-2.0 mm.

8. The method for preparing a heat shock resistant fireproof material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, adding filler, first curing agent and first reaction aid to the first silicone rubber in sequence and stirring evenly to obtain impact-resistant layer glue; S2, adding an inorganic ceramic filler, a coupling agent, an inorganic flame retardant filler, a second reaction aid and a second curing agent to the second silicone rubber in sequence and stirring evenly to obtain a fireproof ceramic layer glue; S3, rolling the fireproof ceramic layer adhesive described in S2 on one side of the glass fiber layer, and coating the impact-resistant layer adhesive described in S1 on the other side to obtain the heat-shock-resistant fireproof material.

9. The method for preparing a heat shock resistant fireproof material according to claim 8, characterized in that: In S2, when the inorganic ceramic filler, coupling agent and inorganic flame retardant filler are added, the temperature of the rubber compound is 80°C-100°C; When the second reaction aid and the second curing agent are added, the temperature of the rubber compound is 15°C-40°C.

10. Use of the heat shock resistant fireproof material according to any one of claims 1 to 7 in new energy power batteries.

Citation Information

Patent Citations

  • Multi-layer fireproof material for battery and manufacturing method of multi-layer fireproof material

    CN112928362A

  • Flame-retardant fire-resistant silicone rubber material and preparation method thereof

    CN118271850A

  • Thermal shock resistant high-refraction LED packaging glue composition and preparation method thereof

    CN106433551A

  • Modified LED packaging silica gel with high refractive index

    CN106947429A

  • Liquid crystal display full lamination high refractive index silica gel

    CN109705802A

Cited By

  • Ceramic polyphosphazene composite material for thermal insulation of power battery and preparation method of ceramic polyphosphazene composite material

    CN121064639A